TIME OF FLOODING FOR GOGO RANCAH RICE AND REPRODUCTIVE STAGE MOISTURE STRESS FOR WALIK JERAMI RICE - Didiek Setio Budi; Bambang Suprihatno (PERHIMPI (Indonesian Association of Agricultural Meteorology), 1994)
Abstract is available in the full text (pdf format)